Advances in agronomy. - Sparks, Donald L., 1953- (Advances in Agronomy, 2023)
Advances in Agronomy, Volume 179, the latest release in this leading reference on agronomy, contains a variety of updates and highlights new advances in the field. Chapters in this new release include Complementing Compost with Biochar for Agriculture, Soil Remediation and Climate Mitigation, Weed Management in Wet Direct-seeded Rice (Oryza sativa L.): Issues and Opportunities, Plant Temperature Response and Heat Tolerance in Rice: A Review, Obstacles in Continuous Cropping: Mechanisms and Control Measures, Agriculture-Related Green House Gas Emissions and Mitigation Measures, and more.